Energy minimization approach for a two-link flexible manipulator - Faris, Waleed Fekry; Ata, A.A; Sa'Adeh, M.Y (Sage, 2009)
Robot motion planning between two given configurations in the time domain has a great impact on robotic applications. In the presence of link flexibility, the problem becomes more difficult and critical to be solved. A two-link flexible manipulator is proposed in this study, where the manipulator's joints are required to undergo a rest-to-rest maneuvering. Two trajectories are assumed, a fourth order polynomial and soft motion trajectories1 the Genetic Algorithm is employed to optimize the unknown parameters of the fourth order trajectory in such away that minimizes the energy consumption during motion. The mathematical model of the manipulator is obtained using the extended Hamilton's principle, where the flexible links are treated using Euler-Bernoulli's beam theory. Simulation study for the optimized joints' torques for the two trajectories is introduced and a comparison between them is carried out based on the minimum energy consumption. © 2009 SAGE Publications.